Pembayaran Ganti Rugi Tanah Jalan Tol Pekanbaru-Kandis Berdasarkan Asas Kepentingan Umum - Andrizal, Andrizal (Jurnal Hukum Novelty, 2018)
The land procurement by the state often raises different opinions about the form or amount of the compensation. The compensation could be done several ways like setting executive compensation, sue the legal problem to the court or others. If the mentioned above do not bring positivelty succeed, then the last alternative is done through deposit for damages to the District Court. This research deals with two problems: 1) how is the implementation of compensation of land procurement by state for highway in Pekanbaru-Kandis; 2) How is the mechanism to compensate the retribution which deposited at the district court. This research approached by legal empirical study and viewed with sociology of law. The results are that the compensation of land authorization by state is done in January 2016 which covers 133 areas. In the case of land mastery dispute and its compensation has been deposited in the district court, it could be taken at court secretariat after the court verdict or based on peace agreement along with cover letter from The Chief Executive of Land Procurement/National Land Agency.